The Effect of Macroeconomic Conditions on Profit Performance and Financial distress in Manufacturing Companies Listed on the Indonesia Stock Exchange - Mitra Riani Aisyah; Muhammad Ali; Mursalim Nohong (Master of Management, Faculty of Economics and Business, Hasanuddin University., 2021)
This study aims to determine the effect of macroeconomic conditions on earnings performance and financial distress in manufacturing companies listed on the Indonesia stock exchange. Variables of macroeconomic conditions are measured by inflation, exchange rates, and interest rates. Profit performance variables are measured by Return on Assets (ROA), and Return on Equity (ROE). Financial distress variables are measured using the Altman Z-Score method. The population in this study is the food and beverage sub-sector manufacturing companies listed on the IDX, and the sampling method uses the purposive sampling method. Data sources in this study are secondary data collected by documentation techniques. This study uses descriptive analysis with a quantitative approach and uses path analysis techniques assisted with Eviews version 9. The results of the study show that (1) inflation and exchange rates have a negative and significant effect on ROA, while interest rates have a negative and not significant effect on ROA; (2) inflation, exchange rates, and interest rates have a negative and significant effect on ROE; (3) ROA and ROE have a negative and significant effect on financial distress; (4) inflation, exchange rates, and interest rates have a positive and significant effect on financial distress; (5) inflation and exchange rates have a positive and significant effect on financial distress through ROA, while interest rates have a positive and not significant effect on financial distress through ROA; (6) inflation, exchange rates and interest rates have a positive and significant effect on financial distress through ROE.